Enhanced or hindered research benefits? A realist review of community engagement and participatory research practices for non-communicable disease prevention in low- and middle-income countries - Ferdinand C Mukumbang; Bipin Adhikari; Deborah Nyirenda; Catherine E Draper; Sonja Klingberg; Priscilla Tiigah; Edna Bosire (BMJ Global Health)
Introduction Community engagement and participatory research are widely used and considered important for ethical health research and interventions. Based on calls to unpack their complexity and observed biases in their favour, we conducted a realist review with a focus on non-communicable disease prevention. The aim was to generate an understanding of how and why engagement or participatory practices enhance or hinder the benefits of non-communicable disease research and interventions in low- and middle-income countries.Methods We retroductively formulated theories based on existing literature and realist interviews. After initial searches, preliminary theories and a search strategy were developed. We searched three databases and screened records with a focus on theoretical and empirical relevance. Insights about contexts, strategies, mechanisms and outcomes were extracted and synthesised into six theories. Five realist interviews were conducted to complement literature-based theorising. The final synthesis included 17 quality-appraised articles describing 15 studies.Results We developed six theories explaining how community engagement or participatory research practices either enhance or hinder the benefits of non-communicable disease research or interventions. Benefit-enhancing mechanisms include community members’ agency being realised, a shared understanding of the benefits of health promotion, communities feeling empowered, and community members feeling solidarity and unity. Benefit-hindering mechanisms include community members’ agency remaining unrealised and participation being driven by financial motives or reputational expectations.Conclusion Our review challenges assumptions about community engagement and participatory research being solely beneficial in the context of non-communicable disease prevention in low- and middle-income countries. We present both helpful and harmful pathways through which health and research outcomes are affected. Our practical recommendations relate to maximising benefits and minimising harm by addressing institutional inflexibility and researcher capabilities, managing expectations on research, promoting solidarity in solving public health challenges and sharing decision-making power.